Advancing and sharing the knowledge base of CT screening for lung cancer - Yankelevitz, David F. (Ann Transl Med, 2016)
CT screening for lung cancer is gaining in acceptance and is now moving from the research domain into standard clinical practice. Coincident with this, there is also increasing awareness of the usefulness of collecting large datasets obtained in the clinical domain and how this can be used to advance practice. Toward this end, in the United States, the Centers for Medicare and Medicaid Services (CMS) are requiring data from screening to be entered into certified registries. While this is still in its early stage and only limited datasets are required, this would be particularly relevant if images as well as clinical information were collected as it will allow for additional evaluation of all imaging findings including ancillary ones and understanding how they integrate into the screening process. All of this needs to be considered in the context of how this information can be shared with a person interested in being screened. In particular, the potential benefit of screening needs to be presented in terms of what is meaningful to the individual including their chances of having lung cancer and also their chance of being cured. This is very different then presenting it in terms of mortality reduction which was never meant to be used for that purpose. Also, how findings made on the CT scans, in addition to those related to lung cancer will be meaningful to them.